Long non-coding RNA MEG3 inhibits cervical cancer cell growth by promoting degradation of P-STAT3 protein via ubiquitination - Zhang, Jun (Cancer Cell Int, 2019)
BACKGROUND: Maternally expressed 3 (MEG3) plays an important role in cervical cancer development, but its exact role remains unclear. Here, we explored the specific regulatory mechanism of MEG3 and its downstream proteins in cervical cancer cells. METHODS: The effect of MEG3 on tumor formation ability of cervical cancer cells was determined in nude mice. The direct binding of MEG3 to phosphorylated signal transducer and activator of transcription 3 (P-STAT3) was detected by RNA pull-down and RNA-binding protein immunoprecipitation (RIP) assays. Cycloheximide (CHX)-chase and ubiquitination assays were performed to determine the regulatory effect of MEG3 on P-STAT3 ubiquitination. Clone formation assay and flow cytometry were used to evaluate the effect of the MEG3-STAT3 regulatory axis on cell proliferation and apoptosis. RESULTS: In vivo tumor formation experiments showed that MEG3 inhibited the tumor formation ability of cervical cancer cells. RNA pull-down and RIP assays demonstrated that MEG3 bound directly to P-STAT3 protein. CHX-chase and ubiquitination assay results showed that MEG3 promoted P-STAT3 degradation via ubiquitination. Clone formation assay and flow cytometry analysis results revealed that the inhibitory effect of MEG3 on P-STAT3 promoted apoptosis and inhibited proliferation of cervical cancer cells. CONCLUSION: MEG3 binds to P-STAT3 in cervical cancer cells, resulting in P-STAT3 ubiquitination and degradation and apoptosis and inhibition of proliferation of tumor cells. The in-depth elaboration of the MEG3-STAT3 regulatory axis in cervical cancer may clarify the mechanism of action of MEG3 and provide new ideas for cervical cancer treatment.